Avoidance of affect in the eating disorders - Lampard, Amy; Byrne, S.; McLean, N.; Fursland, A. (Pergamon, 2011)
The Distress Tolerance Scale (DTS) (Corstorphine, Mountford, Tomlinson, Waller, & Meyer, 2007) measures the tendency to use cognitive and behavioural strategies to manage the experience of positive and negative affect. This paper aimed to explore the factor structure of the DTS, particularly in relation to avoidance of affect. Participants were 227 female university students (non-clinical sample) and 257 clients seeking treatment for an eating disorder (clinical sample). Confirmatory factor analysis was used to test two previously proposed factor structures of the DTS in the non-clinical sample. Both of these models were found to be a poor fit to the data. Subsequently, nine items measuring avoidance of affect were analysed using exploratory factor analysis in the non-clinical sample. Three factors of avoidance of affect were identified (Behavioural Avoidance of Positive Affect, Behavioural Avoidance of Negative Affect, and Cognitive Avoidance of Affect). Confirmatory factor analysis supported this avoidance of affect model in the clinical sample. Significant correlations were observed between avoidance of affect subscales and eating psychopathology in both samples. Results suggest that the avoidance of positive emotion may be an important factor in eating disorders. It is recommended that future studies broaden their investigation of the role of emotion in eating disorders to include both negative and positive emotion.